PENGARUH TINGKAT PROTEIN PAKAN TERHADAP KECERNAAN BAHAN KERING, KECERNAAN PROTEIN KASAR DAN KECERNAAN SERAT KASAR PADA ITIK MOJOSARI JANTAN DAN BETINA PADA PERIODE GROWER - Kaka, Damianus Jama; Marhaeniyanto, Eko; Supartini, Nonok (Fakultas Pertanian, 2018)
Duck is a animal protein both eggs and meat. The aim of this research is to know the Influence of Difference of Protein Level of Feeding to Dry matter Digestion, Crude Protein and Crude Fiber Digestibility of Mojosari Ducks and Grower Period The research was conducted in field laboratory of Agriculture Faculty Tribhuwana Tunggadewi University Malang, on October 30, 2016 - November 20, 2016, while proximate analysis was conducted at the Animal Nutrition and Feed Laboratory of Universitas Brawijaya Malang. The results showed that crude protein digestibility was a significant difference ( P